Telemedicine in Heart Failure During COVID-19: A Step Into the Future - Tersalvi, Gregorio; Winterton, Dario; Cioffi, Giacomo Maria; Ghidini, Simone; Roberto, Marco; Biasco, Luigi; Pedrazzini, Giovanni; Dauw, Jeroen; Ameri, Pietro; Vicenzi, Marco (Frontiers in Cardiovascular Medicine, 2020)
During the Coronavirus disease 2019 worldwide pandemic, patients with heart failure are a high-risk group with potential higher mortality if infected. Although lockdown represents a solution to prevent viral spreading, it endangers regular follow-up visits and precludes direct medical assessment in order to detect heart failure progression and optimise treatment. Furthermore, lifestyle changes during quarantine may trigger heart failure decompensations. During the pandemic, a paradoxical reduction of heart failure hospitalisation rates was observed, supposedly caused by patient reluctance to visit emergency departments and hospitals. This may result in an increased patient mortality and/or in more complicated heart failure admissions in the future. In this scenario, different telemedicine strategies can be implemented to ensure continuity of care to patients with heart failure. Patients at home can be monitored through dedicated apps, telephone calls or devices. Virtual visits and forward triage screen the patients with signs or symptoms of decompensated heart failure. In-hospital care may benefit from remote communication platforms. After discharge, patients may undergo remote follow-up or telerehabilitation to prevent early readmissions. This review provides a comprehensive appraisal of the many possible applications of telemedicine for patients with heart failure during Coronavirus disease 2019 and elucidates practical limitations and challenges regarding specific telemedicine modalities.